Evaluation The Sero-Prevalence of Cytomegalovirus Infection among Abortion Women in Baqubah city - Saja Hussain Kalaf; Zahraa Jaafar Jameel (Academic Science Journal)
Cytomegalovirus (CMV) consider one of the opportunistic viruses, with a worldwide distribution, that can infect humans at any stage of life. It is a major cause of prenatal and perinatal infections and may lead to important complications in pregnancy. This study aims to assess the serum anti-CMV antibody (IgG and IgM) levels in blood of women who suffered abortion and correlation of aborted women with socio-demographic characteristics such as age, living, academic achievement, number of abortion, and fetus age This research was performed between November 2021 and January 2022 on 80 women suffering from abortion and 20 healthy control women in Al-Batool Teaching Hospital in Baqubah city. ELISA test results showed that the abortion women shown highest percentage of seropositive to CMV for IgG (96.3%) and (40%) IgM with a significant difference as compared to the control group (P < 0.05). Anti-CMV IgG and IgM seropositivity were higher in younger women (20-30 years). The current study found that the age group 21-30 years had the highest rate of abortions, with significant differences (P < 0.05). The findings of this study also show that uneducated women, and the women living in rural areas have a higher rate of abortion (58.8% and 72.5%) respectively with significant difference (P < 0.05). Furthermore, the current study found a statistically significant relationship between the number of miscarriages and fetal age, with the highest miscarriage rate for fetuses less than 3 months (98.3%).